Orang Muda Katolik: Antara Moralitas Seksual Dan Trend Pergaulan Bebas - Makasau, Rosmayasinta (Jurnal Masalah Pastoral, 2013)
This study is aimed to gain the Catholic Youth understanding and the implementation of the Christian Sexual morality. The total sample was 24 the Catholic Youth which studied in STK St. Yakobus Merauke at fourth semester. The research method used was descriptive method by using questionaire as the instrument of the research. The result of the research was generally the respondents understood the moral value in Christian Sexuality, in fact they still couldn’t apply in their daily life especially how to reflect it in their attitude toward making date.